Liquid water ionization by fast electron impact: a multiple differential study for the 1B1 orbital - de Sanctis, Maria Laura (2012)
We study theoretically the single ionization of water molecules in a liquid phase by impact of fast electron in a coplanar geometry. For the first time, the wave function for a single water molecule in the liquid phase is described in the realistic way by means of a Wannier orbital formalism. Multiple differential cross sections for the most external 1B1 orbital are obtained through a first-order model within the framework of an independent electron approximation. Moreover, the relaxation of the target is not taken into account. We compare our results with previous theoretical an experimental ones for water in a gas phase. The main physical features of the reaction observed in measurements for vapour (such as binary and recoil peaks) are also observed in our theoretical predictions.